2020
DOI: 10.1111/jcpp.13239
|View full text |Cite
|
Sign up to set email alerts
|

Association between family history of suicide attempt and neurocognitive functioning in community youth

Abstract: Background: Suicidal behavior is highly familial. Neurocognitive deficits have been proposed as an endophenotype for suicide risk that may contribute to the familial transmission of suicide. Yet, there is a lack of research on the neurocognitive functioning of first-degree biological relatives of suicide attempters. The aim of the present study is to conduct the largest investigation to date of neurocognitive functioning in community youth with a family history of a fatal or nonfatal suicide attempt (FH). Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 45 publications
(75 reference statements)
0
7
0
1
Order By: Relevance
“…A family history of suicide is considered a biological and psychological risk factor for family transmission of suicide behavior [29]; some results exist gender differences [30]. Suicide is highly familial, several studies have shown that family contextual factors and family relationships are identi ed as risk factors for suicide ideation and attempts [31]. Adolescents at higher risk commonly have a history of depressive disorder, a previous suicide attempt, and a family history of psychiatric disorders.…”
Section: Discussionmentioning
confidence: 99%
“…A family history of suicide is considered a biological and psychological risk factor for family transmission of suicide behavior [29]; some results exist gender differences [30]. Suicide is highly familial, several studies have shown that family contextual factors and family relationships are identi ed as risk factors for suicide ideation and attempts [31]. Adolescents at higher risk commonly have a history of depressive disorder, a previous suicide attempt, and a family history of psychiatric disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Second, we did not obtain information about family history of STBs. Given previous findings of a significant genetic component predicting suicide attempts (Ruderfer et al., 2019) and neurocognitive differences between youth with a first‐degree biological relative with a history of suicide attempt and matched controls (Jones et al., 2021), obtaining family history of STBs may have yielded important information about subsequent severity of SI. As a related point, recent findings from the Adolescent Brain Cognitive Development Study indicate that high family conflict and low parental monitoring are associated with SI (DeVille et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…15 Furthermore, Jones et al discovered that adolescents with a family history of suicide attempts had greater deficits in executive function, attention and language reasoning compared with those without such a family history. 16 Research has identified common genes overlapping with suicide, impulsivity/risk-taking and major psychiatric disorders. A genome-wide association study by Mullins et al of 1683 individuals who had attempted suicide ('attempters') and 2946 who had not ('non-attempters') with schizophrenia, 3264 attempters and 5500 non-attempters with bipolar disorder and 1622 attempters and 8786 non-attempters with major depressive disorder demonstrated that the polygenic risk score for major depression was associated with suicide attempts in all three disorders.…”
Section: Psychological Genetic and Psychosocial Risk Factorsmentioning
confidence: 99%